Disability-adjusted Life Years (DALYs) for Mental and Substance Use Disorders in the Korean Burden of Disease Study 2012 - Lim, Dohee; Lee, Won Kyung; Park, Hyesook (Journal of Korean medical science, 2016)
The purpose of this study was to estimate the national burden of mental substance disorders on medical care utilization in Korea using National Health Insurance System (NHIS) data and updated disability weight, in terms of disability-adjusted life years (DALYs). For each of the 24 disorders, the incident years lived with disability (YLDs) was calculated, using NHIS data to estimate prevalence and incidence rates. The DisMod-II software program was used to model duration and remission. The years of life lost (YLLs) due to premature death were calculated from causes of death statistics. DALYs were computed as the sum of YLDs and YLLs, and time discounting and age weighting were applied. The year examined was 2012, and the subjects were divided into 9 groups according to age. In 2012, the Korean burden of mental and substance use disorders was 945,391 DALYs. More than 98% of DALYs were from YLDs, and the burden in females was greater than that in males, though the burden in males aged less than 19 years old was greater than that in females. Unipolar depressive disorders, schizophrenia, and anxiety disorders were found to be major diseases that accounted for more than 70% of the burden, and most DALYs occurred in their 30-59. Mental and substance use disorders accounted for 6.2% of the total burden of disease and were found to be the 7th greatest burden of disease. Therefore, mental and substance use disorders need to be embraced by mainstream health care with resources commensurate with the burden.